EFEKTIVITAS PENGAWASAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR CAMAT TORGAMBA KABUPATEN LABUHANBATU SELATAN - Marbun, Budiman; Siagian, Nalom; Pasaribu, Vera (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to describe and describe the efforts of the Torgamba Sub-district Head in improving employee performance and to find out the implementation of the Sub-district Head's supervision in encouraging employee performance achievement. The type of research used is qualitative descriptive research, descriptions of interview results and documentation studies so that it is able to describe various things related to the Effectiveness of Sub-district Head Supervision in Improving Employee Performance at the Torgamba Sub-district Office, South Labuhanbatu Regency. The data obtained were analyzed qualitatively and described in descriptive form. The results of this study indicate that the supervision carried out by the Sub-district Head in improving employee performance at the Torgamba Sub-district Office, South Labuhanbatu Regency is not yet effective enough. Supervision has been carried out, but its intensity still needs to be increased. Supervision carried out by the Sub-district Head such as supervision of attendance, if there are employees who commit violations, they will be given a verbal warning and if it is fatal, they will be given a written warning. However, even though the Sub-district Head has carried out supervision, there are still employees who leave the office without permission even though it is still working hours.